(untitled) (Research, Society and Development, 2020)
The globalized world of the age of digital technologies calls for new spaces for interaction and learning that overcome the limitations of time and space present in the traditional school. Thus, the present study aimed to analyze the perception of professors holding the degree course in Chemistry at IFMT / UAB, EaD modality, regarding the use of technological resources of AVA / Moodle also in the context of classroom teaching. A previous bibliographic review was carried out that supported the elaboration of the research instrument, and the data were obtained by participant observation, and field research through a questionnaire that was applied to 21 (twenty-one) full professors and analyzed by bias. content analysis, with a view to the objectives of the study. The results indicate that the greater access to information, the diffusion of ideas and concepts through the media and the influence of the internet in the teaching and learning processes are factors that have been pressing the school to overcome its traditional teaching paradigm and to approach the operating forces in the world beyond the classroom. The research showed that teachers support initiatives to use ICT in the context of classroom teaching, such as virtual learning environments - VLEs, perceiving technological innovations as positive, and want to make use of their resources, but call for continuing education. in service to enable the technological fluency necessary for the pedagogical use of ICT.